Parenting and media in shaping adolescent prosocial behavior: Evidence from Aceh's Islamic society - Safrilsyah, Safrilsyah; Mahmud, Salami; Muhaini, Muhaini; Hidayati, Siti Hajar Sri (University of Muhammadiyah Malang, 2025)
The rise of digital technology has coincided with growing concerns about a decline in adolescents’ prosocial behavior. This study investigates how parental social support and the use of online media contribute to prosocial tendencies among adolescents in Aceh, Indonesia. A total of 415 students from 12 public and Islamic secondary schools participated in the research, selected through a stratified non-proportional sampling method. Data were collected using three standardized instruments: The Perceived Parental Support Scale, an online media use questionnaire, and the Prosocial Tendencies Measure-Revised. Analyses using multiple regression and t-tests revealed that parental support and online media use significantly predicted adolescents’ prosocial behavior. Together with demographic variables, these factors accounted for 52.9% of the variance in prosocial tendencies (R2 = .529, p < .001). While female students reported higher levels of parental support and media use, male students demonstrated slightly higher levels of prosocial behavior. These results underscore the importance of parental involvement and constructive digital engagement in shaping adolescent morality. The findings call for increased efforts to strengthen family support systems and promote mindful media use to foster positive youth development in the digital era.